Historical Study of the Khaksar Movement’s Interaction with the Muslim League (1931–1947) - Fiaz, Ayesha; Tariq, Saqib (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2025)
Allama Inayatullah Khan Mashriqi founded the Khaksar Movement in 1931 as a social reform initiative rooted in ideals of equality and community service. Over time, however, the movement evolved into a paramilitary force, establishing a complex relationship marked by both cooperation and confrontation with the All-India Muslim League (AIML), led by Muhammad Ali Jinnah. Although both movements aimed to advance Muslim political interests in British India, their methods and ideological foundations differed substantially. Allama Inayatullah Khan Mashriqi envisioned a pan-Islamic Greater Pakistan grounded in religious supremacy and militarization. In contrast, the Muslim League sought to achieve a separate Muslim homeland through constitutional and political means. This division prevented lasting collaboration. Events such as the 1940 Lahore Khaksar massacre, the 1943 attack on Jinnah, and the 1945–46 elections deepened the rift, ensuring the Muslim League’s dominance while leaving Mashriqi’s radical vision unfulfilled. This qualitative study, based on archival sources, examines the nature of cooperation and confrontation between the two movements. It contributes to a deeper understanding of Muslim political mobilization in pre-partition India. It highlights the critical role of ideological coherence and strategic direction in shaping the course and character of political movements.